Adsorption-enforced Fenton-like process using activated carbon-supported iron oxychloride catalyst for wet scrubbing of airborne dichloroethane. (November 2022) - Fu, Chenchong; Pan, Cong; Chen, Tao; Peng, Deqin; Liu, Yaqian; Wu, Feng; Xu, Jing; You, Zhixiong; Li, Jinjun; Luo, Liting
Abstract: Wet scrubbing is a low-cost process for disposing of air pollutants. Nevertheless, this method is rarely used for the treatment of volatile organic compounds (VOCs) because of their poor water solubility. In this study, we used a unique wet scrubbing system containing H2 O2 and activated carbon (AC)-supported iron oxychloride (FeOCl) nanoparticles to remove airborne dichloroethane (DCE). The operating conditions of the wet scrubber were optimized, and the mechanism was explored. The results showed that the adsorption of dissolved DCE onto AC promoted its transfer from air to water, while the accumulation of DCE on AC facilitated its oxidation by OH generated on FeOCl catalyst. The wet scrubber performed well at pH 3 and low H2 O2 concentrations. By pulsed or continuous dosing H2 O2, the cooperative adsorption-catalytic oxidation allowed long-term DCE removal from air. Benefiting from satisfactory cost-effectiveness, avoidance of toxic byproduct formation, and less corrosion and catalyst poisoning, wet scrubbers coupled with cooperative adsorption and heterogeneous advanced oxidation processes could have broad application potentials in VOC control. Graphical abstract: Image 1 Highlights: FeOCl/AC was prepared by a facile calcination method. Wet scrubber containing H2 O2 and FeOCl/AC was effective in dichloroethane removal. Intermittent or continuous dosing H2 O2 allowed long-term VOC removal from air. Adsorption and catalytic oxidation cooperated in the wet scrubbing process.